New Art Forms and Process Management Strategy in an Era of Mass Digitalization - Pavlova, Daniela (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2021)
In ancient times it took centuries before a genre of art was adopted as cultural development (like painting, sculpture etc.), while with the bursting expansion of modern audiovisual forms this process occurs much more frequently, and the need for publicly recognized criteria for evaluating these new media becomes more apparent.
Keywords: Augmented Reality; 3D Objects; Audiovisual Forms; Digital Art; E- Culture Criteria Training